Exogenous human OKSM factors maintain pluripotency gene expression of bovine and porcine iPS-like cells obtained with STEMCCA delivery system - Canizo, Jésica Romina; Vazquez Echegaray, Camila; Klisch, Doris; Aller Atucha, Juan Florencio; Paz, Dante; Alberio, Ricardo; Alberio, Ramiro; Guberman, Alejandra (BioMedCentral, 2018)
OBJECTIVES: The use of induced pluripotent stem (iPS) cells as an alternative to embryonic stem cells to produce transgenic animals requires the development of a biotechnological platform for their generation. In this study, different strategies for the generation of bovine and porcine iPS cells were evaluated. Lentiviral vectors were used to deliver human factors OCT4, SOX2, KLF4 and c-MYC (OKSM) into bovine and porcine embryonic fibroblasts and different culture conditions were evaluated. RESULTS: Protocols based on the integrative lentiviral vector STEMCCA produced porcine iPS-like cells more efficiently than in bovine cells. The iPS-like cells generated displayed stem cell features; however, expression of exogenous factors was maintained along at least 12 passages. Since inactivation of the exogenous factors is still a major bottleneck for establishing fully reprogrammed iPS cells, defining culture conditions that support endogenous OKSM expression is critical for the efficient generation of farm animals' iPS cells.